Composition and Biological Activities of different Date Seed varieties (Phoenix dactylifera) of Oman: Cultivation Zone Influence - Najeeb Ur Rehman,; Hidayat Hussain,; Mohammed Abdullah Al-Broumi,; Mohammed Khiat,; René Csuk,; Ahmed Al-Rawahi,; Abdul Latif Khan,; Fazal Mabood,; Ivan R Green,; Ahmed Al-Harrasi, (International Journal of Phytomedicine, 2017)
Date (Phoenix dactylifera L.) seeds (pits) account for ca. 10% of the date fruit and it is the date pits that present a major problem to the date palm industry in the USA as a waste product. Currently date pits are employed as a food source for animals and poultry, as a soil fertilizer and also as a road base gravel In order to understand the varietal effects of Omani date seeds on the nutritional properties of dates and to explore the use of this waste product from the food industry, twenty two native date seeds (Phoenix dactylifera L.) including the varieties; Qushbu Narenjahn, Fardh, Naghal, Manhi, Qush Balquan, Helali Oman, Khasab, Seedi, Qush Jabrin, Khalas, Qush Basrah, Qushbu Maan, Handal, Khunaizi, Qush Mamoor, Barshi, Barni, Azad, Zabad, Qush Tabak, Qush LuLu, and Halali Alhasa were collected from six regions of the Sultanate of Oman and were examined for their nutritional value, antioxidant and urease properties. Energy values, dry matter, and carbohydrate level were the predominant components examined in the date seeds , followed by fiber, moisture, along with small amounts of ash, protein, and fat. The results of the 22 varieties of date seeds showed a significant energy value of between 283.0 to 407.9 kcal/100g, dry matter of between 93.3%-96.3%, carbohydrate content of between 43.8%-80.6%, moisture in the range of 4.3%-6.6%), fat in the range of 5.0%-10.9%, ash content of between 0.73%-1.08%, protein content of 0.2%-6.9% and fiber content of between 5.0%-32.5%. Furthermore the antioxidant potential ranged between 7.4 - 88.3% depending upon the type of date seeds and location of samples. In this regard the Handal date seeds collected from Al-Hamra showed the highest antioxidant potential with 88.3% inhibition. Similarly urease inhibition ranged from 0.94-70.3% and Qush Tabak date seeds collected from Al-Hamra demonstrated the highest urease potential with 70.3% inhibition. It is noteworthy that Qush Basrah, Seedi, Qush Balquan, and Handal date seeds have significantly higher nutritional attributes compared to the rest in the study group. Moreover Fardh, Khasab, Khalas, and Handal date seeds collected from more than one region of Oman showed variation in some nutritional values. The nutritional analysis further demonstrated the correlation of proximate parameters in different regions of Oman. Results of the current investigation indicate a promising and significant potential for date seeds to be used as a supplementary source of a healthy diet as well as in specific pharmaceutical applications.